Does selective migration alter socioeconomic inequalities in mortality in Wales?: a record-linked total population e-cohort study. (August 2018) - Gartner, Andrea; Farewell, Daniel; Greene, Giles; Trefan, Laszlo; Davies, Alisha; Fone, David; Paranjothy, Shantini
Abstract: Recent studies found evidence of health selective migration whereby healthy people move to less deprived areas and less healthy people move to or stay in more deprived areas. There is no consensus, however, on whether this influences health inequalities. Measures of socio-economic inequalities in mortality and life expectancy are widely used by government and health services to track changes over time but do not consider the effect of migration. This study aims to investigate whether and to what extent migration altered the observed socioeconomic gradient in mortality. Data for the population of Wales (3, 136, 881) registered with the National Health Service on 01/01/2006 and follow-up for 24 quarters were individually record-linked to ONS mortality files. This included moves between lower super output areas (LSOAs), deprivation quintiles and rural-urban class at each quarter, age, sex, and date of death. Cox regression models were used to estimate the hazard ratios for the deprivation quintiles in all-cause mortality, as well as deprivation change between the start and end of the study. We found evidence of health selective migration in some groups, for example people aged under 75 leaving the most deprived areas having a higher mortality risk than those they left behind, suggesting widening inequalities, but also found the opposite pattern for other migration groups. For all ages, those who lived in the most deprived quintile had a 57% higher risk of death than those in the least deprived quintile, allowing deprivation to vary with moves over time. There was little change in this risk when people were artificially kept in their deprivation quintile of origin (54% higher). Overall, migration during the six year window did not substantially alter the deprivation gradient in mortality in Wales between 2006 and 2011. Highlights: Health selective migration was found for selected subgroups. Change to inequalities varied by direction of deprivation change and age group. Migration overall did not alter the socioeconomic gradient in mortality in Wales.